Analisis Kesesuaian Penerapan ISAK 335 dalam Penyusunan Laporan Keuangan Yayasan Kemanusiaan - Rivana Azzahra Nurhidayat; Ghiyats Furqan Dewantara (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Non-profit organization financial reports are a form of accountability to stakeholders, especially donors and the community. This research aims to analyze the suitability of applying ISAK 335 in preparing financial reports at the Humanitarian Foundation. The research uses qualitative methods with a descriptive approach through documentation and document analysis. The research results show that the implementation of ISAK 335 can increase the transparency and accountability of financial reports, although there are still obstacles such as limited understanding of accounting standards and a simple recording system. Financial reports in accordance with ISAK 335 are expected to provide a clearer picture of the financial position and activities of nonprofit organizations. Among the challenges identified is the lack of human resources trained in the application of this accounting standard. Therefore, training and coaching for organizational financial managers is essential. Furthermore, the development of a more modern and integrated financial recording system is also needed to support greater transparency and accountability.